Effects of chronic static stretching interventions on jumping and sprinting performance-a systematic review with multilevel meta-analysis - Warneke, K.; Freundorfer, P.; Plöschberger, G.; Behm, D. G.; Konrad, A.; Schmidt, T. (Frontiers in Physiology, 2024)
When improving athletic performance in sports with high-speed strength demands such as soccer, basketball, or track and field, the most common training method might be resistance training and plyometrics. Since a link between strength capacity and speed strength exists and recently published literature suggested chronic stretching routines may enhance maximum strength and hypertrophy, this review was performed to explore potential benefits on athletic performance. Based on current literature, a beneficial effect of static stretching on jumping and sprinting performance was hypothesized. A systematic literature search was conducted using PubMed, Web of Science and Google scholar. In general, 14 studies revealed 29 effect sizes (ES) (20 for jumping, nine for sprinting). Subgroup analyses for jump performance were conducted for short- long- and no stretch shortening cycle trials. Qualitative evaluation was supplemented by performing a multilevel meta-analysis via R (Package: metafor). Significant positive results were documented in six out of 20 jump tests and in six out of nine sprint tests, while two studies reported negative adaptations. Quantitative data analyses indicated a positive but trivial magnitude of change on jumping performance (ES:0.16, p = 0.04), while all subgroup analyses did not support a positive effect (p = 0.09-0.44). No significant influence of static stretching on sprint performance was obtained (p = 0.08). Stretching does not seem to induce a sufficient stimulus to meaningfully enhance jumping and sprinting performance, which could possibly attributed to small weekly training volumes or lack of intensity.